The Impact of EGDT on Sepsis Mortality in a Single Tertiary Care Center in Lebanon - Christopher El Khuri; Gilbert Abou Dagher; Ali Chami; Ralph Bou Chebl; Tarek Amoun; Rana Bachir; Batoul Jaafar; Nesrine Rizk (Emergency Medicine International)
Background. EGDT (Early Goal Directed Therapy) or some portion of EGDT has been shown to decrease mortality secondary to sepsis and septic shock. Objective. Our study aims to assess the effect of adopting this approach in the emergency department on in-hospital mortality secondary to sepsis/septic shock in Lebanon. Hypothesis. Implementation of the EGDT protocol of sepsis in ED will decrease in-hospital mortality. Methods. Our retrospective study included 290 adult patients presenting to the ED of a tertiary center in Lebanon with severe sepsis and/or septic shock. 145 patients between years 2013 and 2014 who received protocol care were compared to 145 patients treated by standard care between 2010 and 2012. Data from the EHR were retrieved about patients’ demographics, medical comorbidities, and periresuscitation parameters. A multivariate analysis using logistic regression for the outcome in-hospital mortality after adjusting for protocol use and other confounders was done and AOR was obtained for the protocol use. 28-day mortality, ED, and hospital length of stay were compared between the two groups. Results. The most common infection site in the protocol arm was the lower respiratory tract (42.1%), and controls suffered more from UTIs (33.8%). Patients on protocol care had lower in-hospital mortality than that receiving usual care, 31.7% versus 47.6% (p=0.006) with an AOR of 0.429 (p =0.018). Protocol patients received more fluids at 6 and 24 hours (3.8 ± 1.7 L and 6.1 ± 2.1 L) compared to the control group (2.7 ± 2.0 L and 4.9 ± 2.8 L p=<0.001). Time to and duration of vasopressor use, choice of appropriate antibiotics, and length of ED stay were not significantly different between the two groups. Conclusion. EGDT- (Early Goal Directed Therapy-) based sepsis protocol implementation in EDs decreases in-hospital mortality in developing countries. Adopting this approach in facilities with limited resources, ICU capabilities, and prehospital systems may have a pronounced benefit.